2014
DOI: 10.1002/ajoc.201402129
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐Separated Fmoc‐Peptide β‐Sheets: Sequence‐Secondary Structure Relationship for Arranging Charged Side Chains on Both Sides

Abstract: β‐Sheet formation from fluorenylmethoxycarbonyl (Fmoc)‐substituted polar oligopeptides was demonstrated, where acidic and basic side chains are located separately on either side of the β‐sheet surfaces. For yielding such charge‐separated β‐sheets, self‐assembly of 18 pentapeptides was studied, all of which contain glutamic acid (E), lysine (K), and valine (V). Fmoc‐pentapeptides containing one E and one K all formed fibrillar nanostructures consisting of stacked β‐sheets. On the other hand, Fmoc‐pentapeptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…In the case where the sequence or the length of the peptide was modified to Fmoc-KVVVC ( 4 ) and Fmoc-KVVC ( 5 ), ϕ PD were also smaller (ϕ PD = 27.1 and 23.5%, respectively) than that using 1 (Figures c, S6, and S7d and e), possibly because these peptides hardly form β-sheet (Figure S4). Furthermore, when cysteine in 1 was substituted by glutamic acid (E) without metal-binding ability (Fmoc-VKVVE, 6 ), ϕ PD dropped to 19.6% (Figures c, S6, and S7f), which was in a similar level with that using PtNP/GO composite without peptides (ϕ PD = 18.9%, Figure b, orange). On the basis of the relationship of the dye degradation properties and peptide structure (Table S2), we conclude that Fmoc-VKVVC ( 1 ) affords the best photocatalytic dye degradation performance by the formation of β-sheet, which leads to the separation and integration of the functional groups (charged amino groups and metal binding thiol groups) on the opposite surface of the β-sheet (Figure b).…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…In the case where the sequence or the length of the peptide was modified to Fmoc-KVVVC ( 4 ) and Fmoc-KVVC ( 5 ), ϕ PD were also smaller (ϕ PD = 27.1 and 23.5%, respectively) than that using 1 (Figures c, S6, and S7d and e), possibly because these peptides hardly form β-sheet (Figure S4). Furthermore, when cysteine in 1 was substituted by glutamic acid (E) without metal-binding ability (Fmoc-VKVVE, 6 ), ϕ PD dropped to 19.6% (Figures c, S6, and S7f), which was in a similar level with that using PtNP/GO composite without peptides (ϕ PD = 18.9%, Figure b, orange). On the basis of the relationship of the dye degradation properties and peptide structure (Table S2), we conclude that Fmoc-VKVVC ( 1 ) affords the best photocatalytic dye degradation performance by the formation of β-sheet, which leads to the separation and integration of the functional groups (charged amino groups and metal binding thiol groups) on the opposite surface of the β-sheet (Figure b).…”
Section: Resultssupporting
confidence: 54%
“…Peptides were synthesized by an Fmoc solid phase synthesis method (see Methods and Scheme S1). 14,19,20 We have recently reported that Fmoc-VKVVC (1) (V, valine; K, lysine; C, cysteine; Figure 1a) self-assembles to form an antiparallel βsheet in MeOH, where metal-binding thiol groups of cysteine are integrated on one side, while amino groups of lysine are assembled on the other side of the β-sheet (Figures 1b and S1c); the resultant β-sheets showed strong tendency to redisperse agglomerated MNPs. 14 Notably, we found later that, when an aqueous dispersion of PtNPs was mixed with MeOH solution of β-sheet of 1, PtNPs with less than ∼5 nm diameter selectively adsorbed on the β-sheet, while those with larger sizes (>5 nm) were agglomerated (Figure S 1d−f).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peptides functionalized at the N-terminal with large aromatic groups have recently emerged as an exciting class of small molecular hydrogelators. The most used aromatic group is Fmoc. As shown in Scheme , shortly after the report of an unexpected small peptidic hydrogelator made of Fmoc- l -Ala- l -Ala ( 300 ) and Fmoc- d -Ala- d -Ala ( 22 ), Ulijn et al reported the development of Fmoc-diphenylalanine (Fmoc-FF or Fmoc-Phe-Phe ( 6 )), one of the most investigated low molecular weight hydrogelators. The molecules of 6 form hydrogels by adjusting the pH of the aqueous solution of 6 , , by applying 6 to a silica wafer surface, or by the addition of water to a DMSO solution of 6 . , Despite considerable studies on 6 , , it was unclear why the mechanical properties reported for the hydrogels of 6 vary significantly, up to 4 orders of magnitude. To address this inconsistency, Adams et al have systematically studied the mechanical properties of hydrogels of 6 prepared using different protocols.…”
Section: Molecular Designmentioning
confidence: 99%